Population state of black saraguato monkeys (Alouatta pigra) in the Biosphere Reserve of Pantanos de Centla - Pozo-Montuy, Gilberto; Miranda-Chan, Maritza J.; de la Cruz-Córdova, Saul A.; Pinacho-Guendulain, Braulio (Ecosistemas y Recursos Agropecuarios, 2021)
Wildlife conservation requires performing actions based on thesize, composition, and distribution of their populations. This information, however,is incomplete or outdated for many areas of great biological importance. The goalof this study was counting the Black saraguatos (Alouatta pigra) in the BiosphereReserve of Pantanos de Centla (BRPC) to determine their population status. TheReserve was divided into three zones that were censused in 2015, 2016, and 2018by six community monitoring groups. A total of 1 929 saraguatos were counted,of which 57 were solitary individuals and the rest of them were grouped into 362troops with an average size, and standard deviation, of 4.6 ± 2.6 individuals.More than 60% of troops were formed by an adult male, one or more females,and immature individuals. The sex ratio between adult males and females was1:1.2 and the ratio of immature individuals to adult females was 1:1. These resultssuggest that troop size and composition were representative of the species, whilepopulation parameters were within the ranges reported for populations in conservedand fragmented forests. This is the first complete census carried out in a large anddifficult to access area, which emphasize the local people involvement as a strategythat offers advantages during the primate population censuses.